GROSS AND MORPHOMETRICAL STUDIES ON SCAPULA OF STUMP-TAILED MACAQUE (MACACA ARCTOIDES) - Jasvinder Singh Sasan; Kamal Sarma; Shalini Suri (Exploratory Animal and Medical Research, 2020)
The scapula was a flat triangular bone with three borders, three angles and two surfaces. Dorsal border was slightly convex and undulating whereas cranial border was much convex and thinner and ended up distally forming a distinct notch. Posterior border was thick and straight in distal 2/3rd whereas the proximal 3rd was rounded. It presented a distinct groove in the distal 2/3rd. The cranial angle was indistinct. The distal extremity was composed of the elongated glenoid cavity, well developed tuber scapulae and massive coracoid process which was bent postero-medially. The lateral surface was unequally divided by scapular spine into supra-spinous and infra-spinous fossae. The infra-spinous fossa was triangular in outline. The scapular spine ended in a well developed acromion process which was bent cranially. The medial surface lodged a nutrient foramen at its distal part. The maximum length of scapula along the spine (without scapular cartilage) was 7.95 cm for right scapula and 8.04 cm for the left. The maximum width of scapula was 6.35 cm for right scapula and 6.37 for left scapula. The scapular index was 79.8 for the right scapula and 79.22 for the left one. The total length of scapular spine was 8.53 cm and 8.49 cm for right and left scapulae, respectively. The ratio of supra-spinous to infra-spinous fossa was 1:3.4 for right scapula and 1:3.5 for left scapula.